“Nunca peguei um nenê no colo”: traços e pontos sobre gênero construídos por crianças nas suas interações e brincadeiras - Schutz, Litiéli Wollmann (2020)
The main theme of this dissertation is to study gender issues in Early Childhood Education, a look through the games and interactions of young children. It is linked to the Graduate Program in Education, at the Federal University of Santa Maria, and to the research line LP2 - Educational Public Policies, Educational Practices and their Interfaces. This study aims to understand how young children express their understanding of gender issues, through their games and interactions in the context of Early Childhood Education. The methodology is based on a qualitative research, which uses the interpretative approach with principles of ethnographic study and observations that are recorded in the field diary. The research was carried out in an early childhood school, in a pre-B class, composed of seventeen children. A period of three months of participant observation was carried out, three times a week, during the morning shift. For the theoretical basis, authors such as Louro (1996; 2002; 2008), Finco (2003; 2004; 2010; 2013), Scott (1995) were used in relation to gender studies, which they define as a social construction, a concept that helps in understanding the historical and social aspects of the construction of differences between women and men, taking into account their biological difference. Corsaro (2009), Corsino (2009) and Graue and Walsh) (2003) stand out regarding the research methodology with children, who emphasize the importance of listening to what children have to say. For the analysis of the data a range of authors and authors was used as Felipe (1999; 2000; 2004), Brougére (2001), as well as authors of gender studies. This study made it possible to think about gender issues and stereotypes present in society and in the school context, as well as to reflect on the meanings constructed by children about gender conceptions. It was understood that children's understanding of the theme is involved with the family, with culture, with religion, with school and with the media, with society as a whole. In the same way, it was possible to observe the strategies created by the children to break the barriers imposed by society, as in the case of the Tailer boy who, to use makeup, said he painted himself as a clown, after all clowns also use makeup.